A Comparative Study of Map Exploration Interfaces for Multi-Touch Tabletops. Issue 8 (3rd August 2017) - Chen, Ling; Wang, Liwen; Huang, Weikai; Chen, Gencai
ABSTRACT: With the advent of multi-touch tabletops, software developers are creating innovative interfaces for applications such as interactive map systems. In this article, we summarized three representative interfaces from prevalent electronic map applications and literatures—gesture based, widget based, and hybrid, which supported both gestures and widgets—and then compared the effectiveness and the efficiency of these three interfaces by experiments. The results show that the hybrid interface had a better performance, requiring less task-completion time and operations, and causing less arm fatigue. The widget-based interface had the least distance traversed by fingers, but it required many tapping operations. The gesture-based interface was easier to learn compared to the widget-based interface, but the distance traversed during finger movements was the longest. Based on the findings from our experiments, we discuss the implications for the design of map exploration interfaces on multi-touch tabletops.